2022
DOI: 10.1111/jth.15822
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 conformations and mechanism of inhibition in immune thrombotic thrombocytopenic purpura

Abstract: Immune thrombotic thrombocytopenic purpura (iTTP) is an autoimmune disease, caused by autoantibody-mediated inhibition of a plasma metalloprotease ADAMTS13. [1][2][3][4][5] The only known function of ADAMTS13 to date is to cleave the glycoprotein von Willebrand factor (VWF), which recruits platelets to sites of vascular injury for hemostasis. 6,7 In the absence of functional ADAMTS13, ultra-large VWF multimers accumulate and cause a thrombotic microangiopathy that is potentially fatal unless being recognized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…The study samples reflected a broad range of ADAMTS13 activity levels, <1 to 150 IU/dL, with a high number of overall samples ( n = 23) consistent with TTP (i.e., <10 IU/dL ADAMTS13). Several samples were also derived from patients with moderate reductions in ADAMTS13 levels (Figure 2), reflective of the population from which specimens were drawn, being hospitalized sick patients, with inflammation known to modestly reduce plasma ADAMTS13 levels 4,5,33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study samples reflected a broad range of ADAMTS13 activity levels, <1 to 150 IU/dL, with a high number of overall samples ( n = 23) consistent with TTP (i.e., <10 IU/dL ADAMTS13). Several samples were also derived from patients with moderate reductions in ADAMTS13 levels (Figure 2), reflective of the population from which specimens were drawn, being hospitalized sick patients, with inflammation known to modestly reduce plasma ADAMTS13 levels 4,5,33 …”
Section: Discussionmentioning
confidence: 99%
“…Several samples were also derived from patients with moderate reductions in ADAMTS13 levels (Figure 2), reflective of the population from which specimens were drawn, being hospitalized sick patients, with inflammation known to modestly reduce plasma ADAMTS13 levels. 4,5,33 Table 3 summarizes performance characteristics of the Technoscreen assay from this and previous studies. Our study found a high sensitivity (100%) and NPV (100%), which is consistent with previous findings.…”
Section: Accuracy and Reliabilitymentioning
confidence: 99%
“…Hydrogen-deuterium exchange plus mass spectrometric (HX-MS) analysis demonstrates that the anti-spacer domain antibodies, isolated from iTTP patients, bind 5 small flexible loops where vWF binds, suggesting that these antibodies may physically block the interaction between ADAMTS13 enzyme and its substrate vWF ( 69 ). An alternative hypothesis is also possible in which the binding of these antibodies to the spacer domain may result in a conformational change in the catalytic domain, thus affecting the cleavage efficiency of ADAMTS13 protease ( 72 , 73 ). More studies are needed to delineate the mechanism of antibody-mediated inhibition of ADAMTS13 activity.…”
Section: Discussionmentioning
confidence: 99%